Factors Influencing News Purchasing in Tempo - Khairul Anam; Nila A Windasari; Sandhy Widyasthana (LPPM STIE Krakatau, 2025)
Purpose: This study explores the factors that influence purchasing decisions regarding tempo-paid news, namely, individual factors, psychology, and product knowledge. The payment decision variables measured in this research are purchase intention, willingness to pay, and choice of profit model for tempo-paid news. Methodology/approach: This research used a survey method with a purposive sample of 200 non-paid tempo users. The questionnaire consisted of closed choice questions. Data were analyzed by cross-tabulation analysis and chi-square test using the Statistical Package for Social Sciences (SPSS). Results/findings: The findings indicate that individual, psychological, and product knowledge have a significant relationship with purchase intention. Only psychological and product knowledge factors had a significant relationship with willingness to pay. Meanwhile, individual, psychological, and product knowledge factors have a significant relationship with the choice of profit model. This study only reviews the factors that influence purchasing decisions among Tempo non-paid news readers from March to April 2024. Conclusions: Consumer behavior toward paid digital news is influenced by multiple factors, particularly psychological engagement and product familiarity. These insights can guide digital media companies in tailoring content and payment models that align with user preferences and expectations. Limitations: This research was limited to Tempo's paid products, not to other paid news products. Therefore, further research is needed to determine the factors that can influence purchasing decisions on paid news. Nevertheless, the findings provide an initial picture of the factors that influence the purchase of paid news in the Indonesian market, where the model is still young. Contribution: The findings of this research can provide input for future researchers in the marketing discipline or the mass media industry in Indonesia regarding the development of paid news-based business models.